2017
DOI: 10.21037/atm.2017.04.22
|View full text |Cite
|
Sign up to set email alerts
|

Management of strictures after endoscopic submucosal dissection for superficial esophageal cancer

Abstract: Endoscopic resection of early esophageal cancer has a high therapeutic effect while being minimally invasive. Especially, the establishment of the endoscopic submucosal dissection (ESD) procedure has made it possible to resect large lesions in an en-bloc manner. As a result, accurate pathology evaluation became possible, and the risk of local recurrence was extremely low. On the other hand, esophageal strictures after endoscopic treatment of an extensive circumferential lesion are a potential problem. Previous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 22 publications
(25 reference statements)
2
11
0
Order By: Relevance
“…Therefore, it is plausible that our study found a higher incidence of total esophageal stricture due to the high percentage of patients presenting with wide esophageal lesions. Overall, the results of this retrospective study indicate a number of independent risk factors for the development of esophageal stenosis following ESD, which are in line with findings of other studies [13][14][15][16][17][18][19][20][21]. Mizuta et al [13] highlighted that the primary contributor to esophageal stenosis following ESD was the area of periesophageal mucosal defect exceeding 71%.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, it is plausible that our study found a higher incidence of total esophageal stricture due to the high percentage of patients presenting with wide esophageal lesions. Overall, the results of this retrospective study indicate a number of independent risk factors for the development of esophageal stenosis following ESD, which are in line with findings of other studies [13][14][15][16][17][18][19][20][21]. Mizuta et al [13] highlighted that the primary contributor to esophageal stenosis following ESD was the area of periesophageal mucosal defect exceeding 71%.…”
Section: Discussionsupporting
confidence: 89%
“…The proportion of patients who died of esophageal cancer was significantly higher in the RT than in the ES and ET groups. Our results are consistent with the findings of other research, suggesting that aging, T stage, and tumor differentiation are related to a poor prognosis …”
Section: Discussionsupporting
confidence: 93%
“…16,18,19 Serial endoscopic dilations remain the mainstay therapy, but steroid administration via different routes may provide some additional benefit. 19,20…”
Section: Endoscopic Submucosal Dissectionmentioning
confidence: 99%